Sistem PLTS 120 WP dengan Kontrol IoT untuk Monitoring Real-Time Optimasi Irigasi Sawah Berkelanjutan di Kresek Tangerang - Ahmad Putra Pratama; Seflahir Dinata; Ojak Abdul Rozak; Woro Agus Nurtiyanto (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The agricultural sector’s dependence on fossil energy sources such as diesel and electricity from the national grid presents significant challenges, particularly in rural areas with limited energy access, high operational costs, and inadequate infrastructure. These challenges directly affect irrigation systems that require continuous energy supply. To address these issues, this research aims to design and implement a 120 WP Solar Power Plant (PLTS) system equipped with intelligent Internet of Things (IoT)-based control as an environmentally friendly, efficient, and sustainable renewable energy solution to optimize paddy field irrigation in Kresek, Tangerang. The system utilizes monocrystalline solar panels to convert solar energy into electrical energy stored in a LiFePO4 battery, which is then used to power an irrigation water pump. Key components include an inverter, solar charge controller (SCC), ESP32 microcontroller, and several sensors such as INA219 for voltage, ACS712 for current, DS18B20 for temperature, and BH1750 for light intensity. All sensor data is transmitted in real-time and visualized through the Blynk platform, enabling users to monitor system conditions remotely via mobile devices. Experimental results demonstrate that the system operates stably with high efficiency and a sensor error rate of less than 2%. Moreover, the system successfully powers irrigation pumps with consistent output suitable for a 15 m × 12 m field. This research concludes that the IoT-based 120 WP solar power system is an effective solution for supporting clean energy transitions, reducing fossil fuel dependency, lowering agricultural operational costs, and enhancing the productivity and sustainability of irrigation systems in rural farming areas.